Associations Between Birth Characteristics, Weaning Practices, and the Metabolic Syndrome in Children: A Descriptive Study - Teofana Otilia Bizerea-Moga; Tudor Voicu Moga; Ramona Stroescu; Lazar Chisavu; Otilia Mărginean; Flavia Chisavu (Metabolites)
Background: Childhood obesity has seen an important rise in recent decades, in both the pediatric and adult populations. Excess weight can cause various health complications, such as the metabolic syndrome (MetS), a cluster of medical conditions linked to adverse cardiometabolic outcomes. Although MetS may be attributed mainly to adults, early life factors, such as birth characteristics and feeding practices, may influence its development in obese children. Aim: This study aims to investigate the relationships between birth metrics, early feeding practices, and the prevalence of MetS and its components among obese children. Methods: A retrospective observational study was conducted on 800 obese patients aged 0–18 years, admitted to the “Louis Țurcanu” Children’s Clinical and Emergency Hospital in Timișoara, Romania, from 1 January 2013 to 31 December 2023. Patients were divided according to gestational age: small for gestational age (SGA), appropriate for gestational age (AGA), and large for gestational age (LGA). Results: Type 2 diabetes (18.2%), hypercholesterolemia (24.6%), IR (41.3%), and MetS (39.2%) were more prevalent among oSGA patients included in the study. These patients were breastfed for longer periods but weaned at a younger age. oLGA patients had the highest BMI values (28.4 ± 4.2) and, in this study group, hypertriglyceridemia (29.4%), arterial hypertension (26.8%), and lower HDL-C (41.7 ± 6.3 mg/dL) were more prevalent. The incidence of MetS increased with age (12.6 ± 3.1 years). Among these patients, IR (52.3%) was more prevalent. The introduction of flour-based energy-dense foods before six months was more frequent in MetS patients, but not statistically significant. Logistic regression showed oSGA patients had a 4.49-fold higher MetS risk (p < 0.001). Older age at diagnosis increased the risk of developing MetS by 37%, a diagnosis of impaired glucose tolerance by 19-fold, and a family history of diabetes by 2.7-fold. ROC analysis showed strong predictability (AUC = 0.905, sensitivity = 82%, specificity = 88%). Conclusions: Obese children born SGA had a higher risk for developing MetS. The incidence of MetS and its components increases with age among obese patients. Monitoring growth patterns and dietary habits in early life is paramount to mitigate future metabolic complications